English Needs by Hotel Receptionists in Sikka: An Analysis of English for Hospitality - Al-Jufri, Nailil Hikmah; Nasa, Rikardus; Mayaputri, Velmi (Contemporary Education and Community Engagement (CECE), 2024)
The urgency of this research is to improve the quality of hotel services in the Sikka district by identifying hotel receptionist’s needs and challenges in using English. In addition, understanding the English communication needs of hotel receptionists may provide beneficial insight into the industry of hotels and hospitality. This research aims to analyze the English needs of hotel receptionists and identify the importance of using English and the challenges often faced in communicating using English. This research was conducted in several hotels in the Sikka district using qualitative methods. This research employs in-depth interviews with 4 hotel receptionists to gain comprehensive data. The results showed that good English skills are indispensable for receptionists to serve guests more effectively, provide accurate information, handle complaints or special requests from foreign guests, create positive experiences, and support the growth of the hotel business. In addition, this research found that the main challenges faced by receptionists in communicating using English include a lack of technical vocabulary, difficulty understanding different accents and dialects, and constraints in responding quickly and appropriately in emergencies. Solutions to overcome the challenges are continuous and focused English training is essential to overcome these challenges and improve the communication skills of hotel receptionists. In addition, the use of technology such as translator apps can help language obstacles in real-time. In this case, receptionists can be more confident and competent in using English, thus providing better service to international guests.